2021
DOI: 10.1111/jocd.14437
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent herpes zoster after COVID‐19 vaccination in patients with chronic urticaria being treated with cyclosporine—A report of 3 cases

Abstract: Recurrent herpes zoster after COVID-19 vaccination in patients with chronic urticaria being treated with cyclosporine-A report of 3 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…A total of 314 studies were identified. After applying the inclusion and exclusion criteria, 55 studies [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] of VZV manifestations in subjects with SARS-CoV-2 vaccinations or COVID-19 disease were deemed eligible for inclusion. A flow diagram of the selection of the studies is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 314 studies were identified. After applying the inclusion and exclusion criteria, 55 studies [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] of VZV manifestations in subjects with SARS-CoV-2 vaccinations or COVID-19 disease were deemed eligible for inclusion. A flow diagram of the selection of the studies is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…psoriasis, 103 , 133 , 137 , 141 , 215 , 239 , 248 , 252 , 282 , 312 bullous pemphigoid, 63 , 111 pemphigus vulgaris, 111 , 121 lichen planus, 85 , 164 , 245 cutaneous vasculitis, 163 vitiligo 293 and cutaneous lupus erythematosus 156 , 188 , 236 ) and viral reactivation (e.g. herpes zoster 74 , 81 , 85 , 92 , 99 , 100 , 102 , 107 , 108 , 113 , 116 , 131 , 191 , 268 ). In addition, more severe but rare reactions such as anaphylaxis 15 , 37 , 38 , 40 , 41 , 44 , 123 and severe cutaneous adverse reactions (SCARs) 136 , 185 , 231 , 271 have been reported as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent HZ has been observed in chronic urticaria patients treated with cyclosporin-A after COVID-19 vaccination [73].…”
Section: Recurrent Hzmentioning
confidence: 99%